1978
DOI: 10.1901/jeab.1978.30-219
|View full text |Cite
|
Sign up to set email alerts
|

SECOND‐ORDER SCHEDULES OF TOKEN REINFORCEMENT: COMPARISONS OF PERFORMANCE UNDER FIXED‐RATIO AND VARIABLE‐RATIO EXCHANGE SCHEDULES1

Abstract: Rats' lever pressing produced tokens according to a 20-response fixed-ratio schedule. Sequences of token schedules were reinforced under a second-order schedule by presentation of periods when tokens could be exchanged for food pellets. When the exchange period schedule was a six-response fixed ratio, patterns of completing the component token schedules were bivalued, with relatively long and frequent pauses marking the initiation of each new sequence. Altering the exchange period schedule to a six-response va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 20 publications
12
28
0
Order By: Relevance
“…The temporal organization of behavior across the token-reinforcement schedules in the first experiment is similar to that seen in other token-reinforcement schedules with FR tokenproduction and exchange schedules (Kelleher, 1958;Webbe & Malagodi, 1978;Foster et al, 2001;Bullock & Hackenberg, 2006) and in extended-chained schedules with FR components (Jwaideh, 1973). The present experiment sought to more systematically compare tokenreinforcement and extended-chained schedules with respect to both overall response rates and temporal organization of behavior.…”
Section: Methodsmentioning
confidence: 71%
“…The temporal organization of behavior across the token-reinforcement schedules in the first experiment is similar to that seen in other token-reinforcement schedules with FR tokenproduction and exchange schedules (Kelleher, 1958;Webbe & Malagodi, 1978;Foster et al, 2001;Bullock & Hackenberg, 2006) and in extended-chained schedules with FR components (Jwaideh, 1973). The present experiment sought to more systematically compare tokenreinforcement and extended-chained schedules with respect to both overall response rates and temporal organization of behavior.…”
Section: Methodsmentioning
confidence: 71%
“…While extending the use of token systems to new domains, the present study also connects to prior work on extended sequence schedules, including but not limited to token reinforcement schedules. As a type of extended chained schedule, token reinforcement schedules produce temporally organized patterns of behavior, with response rates increasing across token‐production segments leading to the terminal reinforcer (Bullock & Hackenberg, ; Foster et al, ; Waddell, Leander, Webbe, & Malagodi, ; Webbe & Malagodi, ). The differential latencies shown in Figure are consistent with this general finding: Latencies at the outset of token‐production components were consistently longer than those at the outset of exchange‐production components.…”
Section: Methodsmentioning
confidence: 99%
“…For example, an early study by Staats, Staats, Schutz, and Wolf () showed that tokens were effective in generating and maintaining behavior in a reading program with children, even with exchange‐production ratios as high as 24 (i.e., tokens could be exchanged after 24 had been earned). Staats et al also reported evidence of break‐run patterns similar to those obtained with FR exchange‐production schedules with chimpanzees (Kelleher, ), rats (Webbe & Malagodi, ), and pigeons (Bullock & Hackenberg, ; Foster et al, ). The similar schedule‐related effects seen across settings and species suggest that token‐reinforced behavior in the laboratory and in applied settings may be governed by similar principles.…”
Section: Functional Taxonomy Of Token Systemsmentioning
confidence: 69%